Povolání chirurg: pohled pod povrch profese očima chirurgů - Vlastimil Švec; Teodor Horváth; Petr Moravčík; Markéta Španková; Zdeněk Kala (Karolinum Press, 2019)
This study is a probe into the surgical profession from the surgeons' perspective. It presents a qualitative research design drawing from the naturalist tradition based on semi-structured interviews with surgeons. It answers four research questions: 1) Which prerequisites for the surgical profession do surgeons consider important? 2) How do young surgeons learn surgery? 3) Which sources of their professional growth do surgeons note? 4) How can the process of professional growth of a surgeon be characterized? The research questions were a starting point for the analysis of surgeons' answers. Four sets of surgeons' answers were obtained so that their content could be analyzed. Gradually, four smaller sets including answers with similar meaning were obtained. These sets were marked with categories forming the core of interpretations. Research results were organized in accordance with the research questions. One of the most interesting as well as important research results is the design of ten-grade model of surgeons' professional growth including the following ten grades: 1) craft, 2) rules, 3) growth, 4) variation, 5) creativity, 6) mastery, 7) coordination, 8) collaboration, 9) service, 10) fulfilment. The study can be regarded as an example of interdisciplinary collaboration between a teacher and surgeons.